Structure, morphology, and role of primo vascular system - Deby, Deby; Barasila, Atikah Chalida (Bahasa Indonesia, 2025)
Introduction: Kim Bong Han in 1960 introduced the primo vascular system (PVS), a novel circulatory system independent of the circulatory and lymphatic systems. This system is believed to have a relationship with classical acupuncture points and meridians which underlie the mechanism of acupuncture in healing diseases. This study aims to better understand the structure, morphology and role of the primo vascular system.    Methods: This study obtained 30,336 articles from international journals, including Google Scholar, Proquest, Scopus, and Pubmed, focusing on the Primo Vascular System. 12 journals were analyzed, including original English articles published between 2019-2022, open access, and free full text. Results: This study discovered that primo vascular system has a distinct structure and shape in the form of milky-white, semi-transparent spots with primo vessels and primo nodes inside of which primo fluid circulates and contains a variety of cells, including primo microcells that contain DNA. Primo Vascular System can play a role in tissue regeneration, innate immunity in inflammatory processes, and extramedullary hematopoiesis. Conclusion: The primo vascular system, consisting of milky-white, semi-transparent spots with primo vessels and nodes, plays a crucial role in tissue regeneration, innate immunity, and extramedullary hematopoiesis.